Fathers Experience of Paternal Postpartum Depression : A Scoping Review - Alvina Dewi Maharani; Amatullah Mufidah; Anjani Nur Azizah; Arina Dinal Haque; Siti Nurhidayati; Yuli Puspita Devi; Dessy Pratiwi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2025)
Background: Postpartum Depression (PPD) is a mental disorder that occurs within the first year after childbirth, affecting both mothers and fathers. Fathers also experience mood changes during the transition to parenthood, with a significant prevalence of paternal PPD. and a history of mental illness contribute to the occurrence of PPD. Further research is needed to better understand the experiences of fathers dealing with PPD.PPD in fathers has negative effects on family health, including child development, quality of life, and partner relationships. Risk factors such as unemployment, low social support, and a history of mental illness contribute to the occurrence of PPD. Further research is needed to better understand the experiences of fathers dealing with PPD.Objectives: Reviewing the literature discussing fathers' experiences with postpartum depression.Methods: This study is a scoping review using PRISMA to process the article selection. This study for databases source from Pubmed, Wiley, and ScienceDirect, 1.188 articles were obtained from all databases and 4 articles were selected for analysisResults: Based on 4 selected articles with qualitative study design. The results of the study revealed 3 themes containing the, perceptions and emotional experiences of fathers, social support and father relationships, and the search for fathers' mental health support.Conclusion: Postpartum depression (PPD) in fathers has a significant impact on their psychological well-being, resulting in feelings of distress and isolation. Stressors such as work issues and masculinity stigma exacerbate this condition. Therefore, it is important to increase awareness and support from health professionals so that fathers can overcome these challenges.